High-pressure medium-temperature metamorphism of semi-pelitic rocks in the Scotia Metamorphic Complex, Powell Island, South Orkney Islands, Antarctica - Vinagre da Costa, Rodrigo; de Moraes, Renato; Johannes Trouw, Rudolph Allard; Amarante Simões, Luiz Sérgio; Mendes, Julio Cezar (Elsevier, 2019)
The Antarctic continent constituted the southwestern margin of Gondwana until its break-up in the early Cretaceous, when new margins were created along the separating fragments of South America and Antarctica, forming the Scotia Arc. In the Jurassic, part of this passive continental margin became active with subduction of oceanic lithosphere, leading to the introduction of ocean floor material into the accretionary wedge accompanied by deformation and metamorphism. One of these margins is preserved in the South Orkney Microcontinent, and crops out at the South Orkney Islands. At Powell Island, situated in the center of the South Orkney Islands, a gradual transition from very low-grade metarenite, interlayered with metasiltite and slate of the Greywacke Shale Formation, in the south, to biotite-garnet schist, in the north, belonging to the Scotia Metamorphic Complex, is present. The metamorphic map presents from south to north a pumpellyite muscovite chlorite zone, a garnet zone, a biotite-garnet zone and an abundant biotite-garnet zone. Thermobarometric calculations yielded for the garnet and garnet-biotite zones temperatures between 498 and 517 °C with pressures of 9–11 kbar and for the abundant biotite-garnet zone temperatures between 522 and 550 °C and pressures between 11.8 and 13 kbar. These results align well with earlier obtained data for the lower grade rocks and confirm the idea of metamorphism in an accretionary wedge. The relatively high-pressure is interpreted to be responsible for the inversion of the biotite and garnet isograds, for the albitic composition of plagioclase and for the relatively Ca-rich garnet. P-T conditions fall in the transitional field between greenschist, amphibolite, blueschist and eclogite facies.
Keywords: Accretionary prism; Metamorphic petrology; Mineral chemistry; Thermobarometry